2014
DOI: 10.1124/mol.114.093328
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Mapping of an Intracellular Antagonist Binding Site at the Chemokine Receptor CCR2

Abstract: The chemokine receptor CCR2 is a G protein-coupled receptor that is involved in many diseases characterized by chronic inflammation, and therefore a large variety of CCR2 small molecule antagonists has been developed. On the basis of their chemical structures these antagonists can roughly be divided into two groups with most likely two topographically distinct binding sites. The aim of the current study was to identify the binding site of one such group of ligands, exemplified by three allosteric antagonists, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
109
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(117 citation statements)
references
References 47 publications
8
109
0
Order By: Relevance
“…The residues lining the cavity are characterized by moderate to high conservation within the chemokine receptor family, and G 8.47 is conserved in most of them. The fact that some of the intracellularly binding CCR2 antagonists have only moderately weaker potencies against CCR1 (99) and CCR5 (151) supports the existence of the homologous cavity in these receptors. The binding site of several CXCR1 and CXCR2 antagonists was also mapped to a homologous region through mutagenesis (93, 113) and competition binding studies (27).…”
Section: On Allostery Of Chemokine Receptorsmentioning
confidence: 87%
See 2 more Smart Citations
“…The residues lining the cavity are characterized by moderate to high conservation within the chemokine receptor family, and G 8.47 is conserved in most of them. The fact that some of the intracellularly binding CCR2 antagonists have only moderately weaker potencies against CCR1 (99) and CCR5 (151) supports the existence of the homologous cavity in these receptors. The binding site of several CXCR1 and CXCR2 antagonists was also mapped to a homologous region through mutagenesis (93, 113) and competition binding studies (27).…”
Section: On Allostery Of Chemokine Receptorsmentioning
confidence: 87%
“…4a). On the other hand, for CCR2, intracellularly binding synthetic antagonists inhibit binding of the chemokine agonist CCL2 while increasing binding of extracellularly acting antagonists (151, 152). All of these observations are consistent with the idea of chemokine receptors being allosterically regulated “upside-down” and “downside-up” similar to β 2 AR and A 2A AR (Fig.…”
Section: On Allostery Of Chemokine Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of CCR2, the most important residues for binding its intracellular antagonist were found to be the highly conserved tyrosine, Tyr (7.53) (numbering in parentheses represents the Ballesteros residue number (50)), and phenylalanine, Phe (8.50) , of the NPXXYX 5,6 F motif as well as Val (6.36) at the bottom of TM6 and Lys (8.49) in the H8 helix. The -stacking interaction between Phe 312 (8.50) and Tyr 305(7.53) directly links the TM7 and H8 helices and is involved in locking the receptor in an inactive state as observed in several x-ray structures, including that of CCR5 (57). Upon activation of CCR2, the aromatic stacking interaction is disrupted, allowing Tyr 305 (7.53) to rotate into the helical TM core to permit receptor signaling by stabilizing the outward displacement of TM6.…”
Section: Discussionmentioning
confidence: 99%
“…A large amount of site-directed mutagenesis studies, covering almost all chemokine receptors (CCR1, 50,51 CCR2, 15,52,53,93,94 CCR3, 95 CCR5, 5458,90,96−100 CCR8, 59 CCR9, 16 CXCR1, 101103 CXCR2, 60,61 CXCR3, 6367,104 CXCR4, 13,21,6872,74,105114 CXCR7, 115 and US28 75 ) have resulted in 2709 mutation data points, covering 343 different mutants (Figures 10–13, 18–20). About half of the mutation data (1389 data points, covering 238 different mutants) have resulted from studies with 63 unique small-molecule ligands (molecular weight ≤650), of which 46 are shown in Figures 11–13, 18–20.…”
Section: Crystal Structure-based Analysis Of the Effects Of Site-dirementioning
confidence: 99%